We boys together : teenagers in love before girl-craziness - Dennis, Jeffery P. (Vanderbilt University Press, 2007)
"From Andy Hardy and the Dead End Kids to Spin and Marty and Bomba the Jungle boy, romantic relationships between teenage boys were a staple in American popular culture from 1900 through World War II. Here, Jeffery Dennis reveals how masculine, red-blooded, all-American boys were supposed to ignore girls during high school, becoming interested only after graduation, and documents the later shift to the presumption that teenage boys are heterosexually active and aware."--Jacket